KONSEP PERTANDINGAN DAN HADIAH DI DALAM ISLAM - Md Hashim, Ashraf (Jurnal Syariah, 2019)
This article attempts to analyse the relationship between competitions, awards and gambling. Briefly, competitions without awards are allowed as long as they do not violate any Islamic principles. While in general, competitions with awards are also allowed on condition that they fUlfil certain criteria. However, this will depend on the source of the sponsorship of the award. Competitions with awards are allowed when the source of those awards come from the input of non-participants. However, if they are collected from participants themselves, certain guidelines should be followed in order to avoid gambling.